Disharmoni Penetapan Badan Pemeriksa Keuangan dan Putusan Pengadilan dalam Penyelesaian Kerugian Negara terhadap Bendahara: Discrepancies Between the Audit Board Determinations and Court Decisions in the Settlement of State Losses Involving Treasurers - Hudi, Ilham; Agustina, Nia (Badan Pembinaan dan Pengembangan Hukum Pemeriksaan Keuangan Negara Badan Pemeriksa Keuangan RI, 2025)
The Audit Board (BPK) has authority under the Constitution to assess administrative state losses caused by treasurers and to apply a strict liability principle for reparations. In contrast, anti-corruption courts handle corruption cases and rule on a certain amount of state losses; they declare monetary compensation as an additional punitive measure. This study employs a normative legal approach to analyze the discrepancies in assessing the amount of state losses between the two institutions. These disparities impede the effectiveness of recovery of state losses, leading to higher transaction and opportunity costs. This study reveals that the divergence stems from differing methodological approaches: BPK adopts an administrative approach centered on compensation, whereas the courts emphasize punitive measures. This study proposes a multi-track enforcement model as a conceptual solution. It is justified by the cumulative sanctions theory and Article 62 of the State Treasury Law, which provides a legal basis for the simultaneous application of both administrative and criminal sanctions without violating the so-called ne bis in idem principle. This model ensures that criminal verdicts do not relieve the doer of the obligation to compensate for the loss declared by the BPK. Such an approach is essential to accelerate asset recovery, reinforce deterrence, and uphold the integrity of state finances as a top priority in public financial management.